Variables of the digesta in rumen of bulls and bulls of fight with differences in the origin and season of the year in bullfights of the state of Tlaxcala, Mexico - Figueroa, Sara; Hernandez, luz M; Garcia, Guillermina (Acta Universitaria, 2019)
The objective of this study was to evaluate body weight (BW), age, and digestive variables in rumen of animals used at bullfighting events in the state of Tlaxcala for one year. In twenty bullfighting events, the origin (LR: local cattle ranch, located in the state of Tlaxcala; GF: livestock outside the state of Tlaxcala), BW, age (dentition), digestive weight of the rumen, neutral detergent fiber content (NDF), pH, volatile fatty acids (VFA), ruminal protozoal counts and the presence of hepatic abscesses in two study periods (dry and rainy) were recorded. The bulls had a higher BW than the steers (456 vs 361, p ≤ 0.05). In the dry season, a higher BW (432 vs 405, p ≤ 0.05) was recorded than in the rainy season, presenting statistical interaction between the classification (steer or bull) and the station (p ≤ 0.05). GF animals had higher digesta contents than LR (8.1 vs 7.25%, p ≤ 0.05). The pH of rumen fluid was lower for steers compared to bulls (5.86 vs 6.54, p ≤ 0.05) as well as the NDF (61.2 vs 64.7, p ≤ 0.05). In conclusion, steers presented greater problems with ruminal acidosis than bulls. The bullfighting regulations based on the weight and age of the animals are not properly applied by the authorities.